PEMBANGUNAN SISTEM INFORMASI MANAJEMEN SURAT MENYURAT DENGAN METODE PERSONAL EXTREME PROGRAMMING (PXP) DI LINGKUNGAN INSTITUT TEKNOLOGI KALIMANTAN - Muhammad Kharisma; Muhammad Fathurrohim; Bima Catur Apriadi (LPPM ITK, 2022)
Today, every company and organization must deal with the responsibility of having to use information technology. The current state of information technology is generally intertwined with all activities, regardless of whether they are carried out within a business or an organization. Information technology is a collection of tools used to handle information processing jobs and process information. Susilo Bambang Yudhoyono, the sixth president of the Republic of Indonesia, opened the Kalimantan Institute of Technology on October 6, 2014, the same day it was formed as one of Indonesia's newest state colleges in the province of East Kalimantan. The Kalimantan Institute of Technology is still developing higher education at this time. ITK has been working to prepare the organization and work procedures since 2012 by incorporating current resources and establishing standardized administrative systems. Organizational structures and work processes are carried out in accordance with established protocols, namely by adopting a structure and process that adheres to the principles of Good University Governance (GUG). The accomplishment of the organization's aims and objectives is guaranteed by the right organization and work procedures within the organization and work procedures. To ensure that all roles work together to fulfill ITK's objectives, resource management attempts to make clear the lines of coordination and synergy in the organization and work processes. Personal Extreme Programming (PXP) is the methodology used in this study. Literature review, problem formulation, requirements, planning, coding, design, system testing, retrospective, deployment, and user training are the processes of putting this research into practice. The publication in the journal J-Sakti (Journal of Computer Science & Informatics) with authorized rank 4 and the posting of one scientific paper on the LPPM ITK website are the research's output goals. The results obtained from this study are a Website-based Correspondence Information System that accommodates the performance of education staff in the Kalimantan Institute of Technology.